Diet and exercise reduce low-grade inflammation and macrophage infiltration in adipose tissue but not in skeletal muscle in severely obese subjects - Bruun, Jens M; Helge, Jorn W; Richelsen, Bjorn; Stallknecht, Bente (American journal of physiology: endocrinology and metabolism, 2006)
1 Department of Endocrinology and Metabolism C, Aarhus University Hospital, Aarhus Sygehus, Aarhus C; and 2 Copenhagen Muscle Research Centre, Department of Medical Physiology, The Panum Institute, University of Copenhagen, Copenhagen N, Denmark Submitted 9 December 2005 ; accepted in final form 12 December 2005 Obesity is associated with low-grade inflammation, insulin resistance, type 2 diabetes, and cardiovascular disease. This study investigated the effect of a 15-wk lifestyle intervention (hypocaloric diet and daily exercise) on inflammatory markers in plasma, adipose tissue (AT), and skeletal muscle (SM) in 27 severely obese subjects (mean body mass index: 45.8 kg/m 2 ). Plasma samples, subcutaneous abdominal AT biopsies, and vastus lateralis SM biopsies were obtained before and after the intervention and analyzed by ELISA and RT-PCR. The intervention reduced body weight ( P < 0.001) and increased insulin sensitivity (homeostasis model assessment; P < 0.05). Plasma adiponectin ( P < 0.001) increased, and C-reactive protein ( P < 0.05), IL-6 ( P < 0.01), IL-8 ( P < 0.05), and monocyte chemoattractant protein-1 ( P < 0.01) decreased. AT inflammation was reduced, determined from an increased mRNA expression of adiponectin ( P < 0.001) and a decreased expression of macrophage-specific markers (CD14, CD68), IL-6, IL-8, and tumor necrosis factor- ( P < 0.01). After adjusting for macrophage infiltration in AT, only IL-6 mRNA was decreased ( P < 0.05). Only very low levels of inflammatory markers were found in SM. The intervention had no effect on adiponectin receptor 1 and 2 mRNA in AT or SM. Thus hypocaloric diet and increased physical activity improved insulin sensitivity and reduced low-grade inflammation. Markers of inflammation were particularly reduced in AT, whereas SM does not contribute to this attenuation of whole body inflammation. adipokines; macrophages; adiponectin; weight loss; exercise Address for reprint requests and other correspondence: J. M. Bruun, Dept. of Endocrinology and Metabolism, Aarhus University Hospital, Aarhus Sygehus, Tage Hansensgade 2, DK-8000 Aarhus C, Denmark (e-mail: Jens.Bruunatki.au.dk )